Microanatomic analyses of extratemporal facial nerve and its branches, hypoglossal nerve, sural nerve, and great auricular nerve - Ibrahim Erdim; Veysel Gurbuz; Emrah Sapmaz; Selcuk Cetin; Fikret Gevrek (Brazilian Journal of Otorhinolaryngology, 2023)
Objective: To investigate microanatomic organizations of the extratemporal facial nerve and its branches, hypoglossal nerve, sural nerve, and great auricular nerve. Methods: Nerve samples were dissected in 12 postmortem autopsies, and histomorphometric analyses were conducted. Results: There was no significant difference between the right and left sides of the nerve samples for the nerve area, fascicle area, number of fascicles and average number of axons. The lowest mean fascicle number was found in the hypoglossal nerve (4.9 ± 1.4) while the highest was in great auricular nerve (11.4 ± 6.8). The highest nerve area (3,182,788 ± 838,430 μm2), fascicle area (1,573,181 ± 457,331 μm2) and axon number (14,772 ± 4402) were in hypoglossal nerve (p < 0.05). The number of axons per unit nerve area was higher in the facial nerve, truncus temporofacialis, truncus cervicofacialis and hypoglossal nerve, which are motor nerves, compared to the sural nerve and great auricular nerve, which are sensory nerves (p < 0.05). The number of axons per unit fascicle area was also higher in motor nerves than in sensory nerves (p < 0.05). Conclusion: In the present study, it was observed that each nerve contained a different number of fascicles and these fascicles were different both in size and in the number of axons they contained. All these variables could be the reason why the desired outcomes cannot always be achieved in nerve reconstruction.